Determination of Morphine and Codeine in Human Urine by Gas Chromatography-Mass Spectrometry - Xiaoqian Zhang; Mengchun Chen; Gaozhong Cao; Guoxin Hu (Journal of Analytical Methods in Chemistry)
A sensitive and selective gas chromatography-mass spectrometry (GC-MS) method was developed and validated for the determination of morphine and codeine in human urine. The GC-MS conditions were developed. The analysis was carried out on a HP-1MS column (30 m × 0.25 mm, 0.25 μm) with temperature programming, and Helium was used as the carrier gas with a flow rate of 1.0 mL/min. Selected ion monitoring (SIM) mode was used to quantify morphine and codeine. The derivation solvent, temperature, and time were optimized. A mixed solvent of propionic anhydride and pyridine (5 : 2) was finally used for the derivation at 80°C for 3 min. Linear calibration curves were obtained in the concentration range of 25–2000.0 ng/mL, with a lower limit of quantification of 25 ng/mL. The intra- and interday precision (RSD) values were below 13%, and the accuracy was in the range 87.2–108.5%. This developed method was successfully used for the determination of morphine and codeine in human urine for forensic identification study.